2017
DOI: 10.1007/s11605-016-3304-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Versus Delayed Cholecystectomy After Percutaneous Transhepatic Gallbladder Drainage in Grade II Acute Cholecystitis Patients

Abstract: PTGBD and ELC are highly efficient in resolving cholecystitis sepsis. Delayed cholecystectomy after PTGBD produces better outcomes with a lower conversion rate, fewer procedure-related complications, and a shorter hospital stay than emergency cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…That said, one study reported that the differences were not substantial between the two approaches . Furthermore, two studies comparing surgery after PTGBD to early surgery without PTGBD (one randomized controlled trial and one cohort study ) both reported good outcomes when Lap‐C was performed after waiting 4–6 weeks after PTGBD for the factors bleeding volume, operating times, percentage of patients switched to open surgery, and incidence of complications. These results suggest that risks may be increased further when Lap‐C is performed at a relatively early stage after PTGBD in high‐risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…That said, one study reported that the differences were not substantial between the two approaches . Furthermore, two studies comparing surgery after PTGBD to early surgery without PTGBD (one randomized controlled trial and one cohort study ) both reported good outcomes when Lap‐C was performed after waiting 4–6 weeks after PTGBD for the factors bleeding volume, operating times, percentage of patients switched to open surgery, and incidence of complications. These results suggest that risks may be increased further when Lap‐C is performed at a relatively early stage after PTGBD in high‐risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…AC patients may present with a wide spectrum of disease severities linked to the operative difficulty, leading to the possibility of bile duct injury when AC patients undergo LC [2][3][4]. Several studies have also endorsed the usefulness of PTGBD for AC with a high success rate of efficacious drainage and a low complication rate, making it is a suitable treatment for AC patients [29,30,36].…”
Section: Discussionmentioning
confidence: 99%
“…Among these 25 articles, 10 were excluded because of a lack of a control group (n = 7) and necessary data (n = 3). Finally, 15 articles were included in this meta-analysis [3,4,6,10,[15][16][17][28][29][30][31][32][33][34][35].…”
Section: Literature Retrieval and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations